PIC Signboard / Mohd Shuib Zainal Abidin - Zainal Abidin, Mohd Shuib (2005)
PIC Gallery Signboard is design to be function like an electronic signboard that can give any information that has been programmed. It has many functions such as traffic light scoreboard at stadium, signboard at LRT station and also at KL1A for example, in LRT station the signboard shows the lime of the train will arrive and departure. The signboard also was \ci\ useful especially during night and raining because in this lime the driver’s view is limited. The electronic signboards use a bright LED that the drivers can easily see the direction or instruction in the signboard. This signboard was widely used in many places especially in big city like Kuala Lumpur. In Kuala Lumpur, this electronic signboard was widely used in many streets It is also functioned as a traffic light This signboard can be designed using the PIC programmer It is an empty 1C that can be programmed by using the software programmed. The 4 bits binary code was very important to he studied and know and programmed the circuit. This project will introduce the electronic signboard with PIC16F84A. The message is displayed to How' from right to left 128 s LEI) is used for this signboard. The display is based on what we programmed it into the 1C.